Effects of an 8-Week Structured Physiotherapy Program on Health-Related Quality of Life and Walking Speed in a Child Following Rotationplasty: A Case Study - Tamboosi, Mohammad; Altafir, Faris; Alshehri , Asma; Alharthi, Hashim (J Med Rehab Sci, 2025)
Rotationplasty is a limb-saving surgery for children with osteosarcoma, but it can have complications. This study aimed to investigate the impact of early physiotherapy on functional recovery in a child who underwent rotationplasty for femoral osteosarcoma. A 12-year-old boy received rotationplasty for the treatment of left distal femoral osteosarcoma. A comprehensive physiotherapy program was implemented, commencing immediately post-operatively and progressing through a series of stages tailored to the patient’s evolving functional capacity. Patient health status and functional mobility, specifically QE-5D-5L and 10-meter walk test performance, were assessed at multiple time points. Significant improvements were observed in both health status and walking speed. These findings suggest that early initiation of physiotherapy, incorporating strengthening exercises, gait training, and balance activities, are crucial for optimizing functional outcomes in pediatric patients following rotationplasty.